Distribution of Water Phantom BNCT Kartini Research Reactor Based Using PHITS - Nunung Gupita Ratnasari; Susilo Susilo; Yohannes Sardjono (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2018)
The purpose of this research was to calculate the radiation dose on BNCT. Boron Neutron Capture Therapy (BNCT) is a cancer therapy which utilizes thermal neutron-capture reactions by boron-10 isotopes that produce alpha particles and lithium nuclei. The advantage of BNCT is that radiation effects can be limited to tumor cells. The dose of radiation on BNCT depends heavily on the distribution of boron and the neutron free region. The calculation method involves alpha and lithium particles of reactions having high Linear Energy Transfer (LET). By replacing the target of using water phantom that contains heavy water and covered by acrylic glass measuring 30 cm x 30 cm x 30 cm, the dose is calculated using PHITS-based applications. By comparing the simulation results between boron and phantom water or phantom without boron then the conclusion is the absorbed dose of phantom water containing boron is larger than phantom water without boron.